The judo World Ranking List and the performances in the 2012 London Olympics - Franchini, E.; Julio, U. F. (Asian Journal of Sports Medicine, 2015)
Background: In 2009, the International Judo Federation (IJF) created a World Ranking List (WRL) to classify athletes according to their performance in international-level competitions and to qualify athletes for the Olympic Games.